STUDI PERBANDINGAN DISAIN STRUKTUR ATAS JEMBATAN BETON DENGAN JEMBATAN KOMPOSIT PADA PROYEK PEMBANGUNAN JEMBATAN PARALAYANG - Rizky Haris Nugraha (PROCEEDING STIMA)
The construction of the Paralayang Bridge is a new access road bridge between Cibatu and Ciande. In the process of building a bridge, there are using the old technology of concrete girder bridge and new technology is a composite girder bridge that has its own advantages and disadvantages, to determine which methods and technologies will apply the researcher must be smart to sort out and choose for the planning of paralayang bridge construction. This study aims to design a paralayag bridge looking for shear forces and momentsThe result of this research has the difference of heavy concrete bridge because girdle and diaphragm made of concrete obtained the ultimate shear force of 627.02 KN and ultimate moment of 1601.77 km. While the composite bridge is lighter because the girder is made of IWF steel and there is no diaphragm, the ultimate shear force is 549,92 KN, and the ultimate moment is 1393,66 KN.